ANALYSIS OF READINESS FOR THE IMPLEMENTATION OF SCHOOL BASED MANAGEMENT AT SD NEGERI 195 PALEMBANG (SWOT ANALYSIS APPROACH) - Rossa Ramadhona; Reni Yunus; Komariah Hawa; Rosmerry Simanjuntak; Siti Juariah; Mohamad Pandu Ristiyono (SAJMR : Southeast Asian Journal of Management and Research, 2024)
This research delves into the Analysis of Readiness for the Implementation of School-Based Management (SBM) at SD Negeri 195 Palembang using a SWOT Analysis Approach. The study focuses on assessing the school's preparedness to implement SBM, considering internal strengths and weaknesses, as well as external opportunities and challenges. By evaluating factors such as technical readiness, professionalism readiness, and psychological readiness, the research identifies the school's position in terms of readiness for SBM implementation. The findings reveal that SD Negeri 195 Palembang demonstrates strong readiness in implementing SBM, particularly in terms of school autonomy, management information systems, leadership, teamwork, and stakeholder participation. The study emphasizes the importance of comprehensive action plans, stakeholder engagement, continuous capacity building, financial transparency, fostering innovation, and monitoring progress to ensure successful SBM implementation. Through a qualitative research approach, the study highlights the significance of analyzing readiness before implementing SBM to enhance effectiveness and efficiency in educational processes. By following the recommendations proposed in the research, SD Negeri 195 Palembang can navigate challenges, promote excellence, and elevate the quality of education provided to its students. This research contributes valuable insights to the field of educational management and SBM implementation strategies